Effect of diamond particles on the microstructure and composition of pulse plated multilayer Ni-W/diamond composite coatings - Das Malay Kumar; Qin Jiaqian; Karn Priya (MATEC Web of Conferences, 2019)
The research encompasses the fabrication of multilayer Ni-Wdiamond composite deposits by pulse current electrodeposition. The mean surface diameter of the diamond used for the research was 0.9 microns. The composites were fabricated under various conditions and characterized by means of SEM, EDS and XRD to investigate and analyze their microstructure, grain size and elemental distribution along with variations in morphology under different conditions. The effect of variations in forward and reverse current density along with duty cycle and the combination of various aforesaid conditions on the coatings were studied and analyzed.